Avaliação da qualidade dos tratamentos endodônticos, na etapa da obturação, realizados por alunos de graduação - Fritz, Ana Lia Campos (2017)
The objective of the present study was to evaluate, by means of periapical radiographs, endodontic treatments in the obturation phase, carried out by undergraduate students of the Federal University of Espírito Santo, during the course of Endodontics II, from 2012 to 2014. The radiographic records of 511 endodontic treatments were submitted to the inclusion criteria, including preoperative and postoperative periapical radiographs of uniradicular and birradicular teeth with adequate processing and technique quality; the criteria of exclusion were represented by radiographs with errors of processing and/or technique that made an analysis by examiners impossible, other than roots containing resorptions, calcifications, perforations, deviations or fractured instruments inside them and retreatments. Thus a final sample of 368 teeth and 442 root canals was determined. The radiographs were analyzed by three pre-calibrated examiners with the help of an image overhead projector. The criteria used for the analysis was length and density. When one of the criteria was considered inadequate, the endodontic treatment was classified in the same way. The data was recorded and submitted to statistical analysis using the chi-square test and a significance level of 5%. Teeth with adequate fillings were found in 93.75% of the cases. Regarding density, 2.98% of fillings were considered inadequate. Regarding the length, 1.35% of the cases were observed as overfilled and 2.17% underfilled. There was no statistically significant difference (p> 0.05) between the groups of teeth (incisors, canines and premolars). It was concluded that fillings carried out by undergraduate students of the Federal University of Espírito, from 2012 to 2014, were considered to be adequate.